اختيار طرق تصنيع و تجميع القطع النموذجية الوظيفية على آلات التشغيل المبرمجة بالاعتماد على مراكز القرار - علي هتره; تمام سلوم (Tishreen University, 2019)
This paper presents the manufacturing process for complex parts in the aim of building functional prototype mechanisms. Functional prototypes are used during testing in order to validate new product design. Their layouts are very similar to the final product, wherein lies the interest of testing many modifications. The mechanism must respect the functional geometrical requirements and be capable of withstanding forces or, for example, ensuring a tight seal. The principle being proposed consists of decomposing the complex parts into several simple ones that can then be manufactured on a five-axis, high-speed milling machine from thick (approximately 40 mm) sheets made of resistant materials, notably aluminum. The problem at hand is threefold: the choice of slicing in order to avoid cutting functional areas; the choice of both positioning mode and sheet fastening mode; and lastly, the choice of machining process. تعرض هذه المقالة طريقة التصنيع السريع للنموذج URP   Usinag Raide de Prototype من أجل تصميم وتصنيع القطع الميكانيكية المعقدة وذلك لإنتاج الميكانزمات النموذجية الوظيفية. تعتمد هذه الطريقة على تقسيم القطع المعقدة إلى عدة قطع بسيطة قابلة للتصنيع على آلات التشغيل المبرمجة ذات السرع العالية انطلاقا من قطع خام ذات سماكات مقبولة تقريبا̋ 40 مم من مواد مقاومة و خاصة الألمنيوم. سوف نعرض في هذه المقالة كيفية اختيار نوع التوضع (السنترة) و التثبيت للشرائح المتعددة بعد اختيار مستويات التقطيع في المرحلة الاولى بعد ذلك سنوضح كيفية اختيار طرق التصنيع للشرائح على مثبتات قياسية على آلات التشغيل المبرمجة وقابلية التشغيل لهذه الشرائح.